Low cost, simple analytical method to determine the purity and strength of costly Ayurvedic ingredient Hirabol (commiphora myrrh) from various samples.: Array - MAHESH ATALE, MAHESH (Ayurline: International Journal of Research in Indian Medicine, 2021)
Ayurveda is the holistic science of life. In ancient scriptures of Ayurveda, medicinal properties of Hirabol has been described. In recent years, entire world is looking forward for the use of medicinal plant products in healthcare system. Analysis and standardization of drug is todays need. The herbal industry needs to follow strict guidelines and regulations as laid down by the government. The use of Hirabol is mentioned in various ayurvedic literatures. Since ancient time it has been used as a household remedy. The analysis of Hirabol or Myrrh is not specified in any of the authentic books because of the lack of proper method. Modern methods involve high cost apparatus and hence are beyond reach of common Vaidya. By using simple solvent extraction methods and available tests, here is an attempt made to analyze the purity and strength of Myrrh using various samples available in Indian Market.